Finger Puppet Learning Media Based on Character Cards to Enhance Early Childhood Speaking Abilities - Umar, Wirda Saputri; Rosdiana, Rosdiana; Hasis, Pertiwi Kamariah (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2024)
This research is motivated by the lack of development in children's speaking skills, as observed in classroom learning processes. One contributing factor is the limited use of interactive learning media and tools that can stimulate children's speaking abilities. Therefore, finger puppet media based on character cards was developed using the ADDIE model, aimed at improving the speaking abilities of children in Class B at Negeri Pembina Larompong Kindergarten. Data were collected through observation, interviews, and validation by experts and analyzed using descriptive quantitative methods. Based on the research results, the developed media received a score of 88% from material experts and 87.14% from media experts, which falls into the "very valid" category. The use of this media is expected to assist teachers in effectively and enjoyably stimulating children's speaking abilities as an interactive learning tool.